2016
DOI: 10.1080/09581596.2016.1249826
|View full text |Cite
|
Sign up to set email alerts
|

The assets-based approach: furthering a neoliberal agenda or rediscovering the old public health? A critical examination of practitioner discourses

Abstract: The ‘assets-based approach’ to health and well-being has, on the one hand, been presented as a potentially empowering means to address the social determinants of health while, on the other, been criticised for obscuring structural drivers of inequality and encouraging individualisation and marketisation; in essence, for being a tool of neoliberalism. This study looks at how this apparent contestation plays out in practice through a critical realist-inspired examination of practitioner discourses, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The study also revealed the circumstances in which an appropriate blend of emotional involvement and detachment tended to interpretations of and practice with residents, which suggests that working conditions can be developed to foster this. This is endorsed by Roy (2016) who saw that, in the context of asset-based community development, workers in Scotland were able to exploit the neoliberal agenda and work around it by supporting communities to work together to mitigate the effects of poverty. Figurations of social relations are in a constant state of flux (Elias, 1991), highlighting the fact that practices can and do shift under changing circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed the circumstances in which an appropriate blend of emotional involvement and detachment tended to interpretations of and practice with residents, which suggests that working conditions can be developed to foster this. This is endorsed by Roy (2016) who saw that, in the context of asset-based community development, workers in Scotland were able to exploit the neoliberal agenda and work around it by supporting communities to work together to mitigate the effects of poverty. Figurations of social relations are in a constant state of flux (Elias, 1991), highlighting the fact that practices can and do shift under changing circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Nancy Krieger (2008, p. 223) reminds us that our “understanding of the societal distributions of health … cannot be divorced from considerations of political economy and political ecology”. Whether there is something implicit within social enterprises that enables them, or at least makes them potentially suitable, to address such structural factors, or whether their impact is constrained to dealing with (downstream) symptoms of problems alone, is a topic that deserves much closer critical examination (although see Roy (2016) and particularly Roy and Hackett (2016) for a full discussion). Glasgow also has a very specific health profile, and highly developed social enterprise sector.…”
Section: Discussionmentioning
confidence: 99%
“…This is a finding that echoes debates about commissioning public services from the third sector more generally, which suggests that in practice, service provision may be more 'business as usual' than radically different. What happens in practice is a contingent outcome of local networks as much as policy drivers 16,17 , and public health practitioners working within social enterprises may not be doing anything different in practice from those in other types of organisation 18 . Despite its limited geographical scope, and reliance on reports of practice, the findings of the present study document a growing role for social enterprises in public health provision, with risks and potential benefits that need further exploration at the level of population health.…”
Section: Discussionmentioning
confidence: 99%